Vesicovaginal fistula with surgical interventions at Dr. Ramelan Naval Hospital, Surabaya, Indonesia - Ayudelvi, Sahika Nisandi; Najmi, Risa; Amala, Ritma Visi; Ramadina, Rizka Indah; Konitatunisa, Salma Inas; Herdiyantini, Mita; Ardiana, Dian (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Vesicovaginal fistula (VVF) cases in this study were primarily caused by hysterectomy, post-caesarean section surgery, and radiation therapy for cervical cancer. Symptoms experienced by patients included urine leakage from the vagina, foul odor, and pain during urination. The success rate of fistula repair using cystography and fistula repair procedures was very high. The patients were able to urinate normally without pain or vaginal leakage.   ABSTRACT Objective: Evaluating the risk factors and outcomes of surgical interventions in patients with vesicovaginal fistula at Dr. Ramelan Naval Hospital Surabaya, Indonesia, from January 2019 to December 2023. Case Series: There were 6 cases of vesicovaginal fistula that underwent surgical interventions at Dr. Ramelan Naval Hospital, Surabaya, from 2019 to 2023 that met the inclusion criteria. The majority of vesicovaginal fistula cases occurred as a result of hysterectomy, accounting for 4 cases (67%), followed by caesarean section surgery (16%) and radiation therapy for cervical cancer (17%). Symptoms experienced by the patients included urine leakage from the vagina, foul odor, and pain during urination. The vesicovaginal fistulas that underwent surgical interventions were typically 0.5 to 3 cm in size. Most of the cases involved simple-type fistulas. A total of 5 cases (83%) were successfully repaired. These patients were able to urinate normally, without pain or vaginal leakage. However, 1 case (17%) experienced recurrent fistula with an increase in the number of fistulas and continued to experience pain during urination and leakage from the vagina, particularly during strenuous activities. Conclusion: The vesicovaginal fistula cases at Dr. Ramelan Naval Hospital Surabaya, Indonesia, from 2019 to 2023 showed a high therapeutic success rate. Among 6 patients that we studied, the majority of cases were caused by hysterectomy, characterized as simple-type fistulas, with 83% of the cases were successfully repaired.